PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN MASYARAKAT PENGGUNA LAYANAN PADA KANTOR URUSAN AGAMA KECAMATAN KARAU KUALA TAHUN 2022: THE EFFECT OF SERVICE QUALITY ON COMMUNITY SATISFACTION OF SERVICE USERS IN THE RELIGIOUS AFFAIRS OFFICE, KARAU DISTRICT, KUALA IN 2022 - Kurniaty, Harlina (Pencerah Publik, 2022)
Abstrak Kualitas Pelayanan merupakan sebagai ukuran seberapa bagus tingkat layanan yang diberikan mampu terwujud sesuai harapan pengguna. Kualitas Layanan itu sendiri ditentukan oleh kemampuan Instansi dalam memenuhi kebutuhan dan keinginan pengguna sesuai dengan ekspektasi pengguna. Kepuasan Masyarakat merupakan kegiatan pengukuran secara komprehensif tentang tingkat kepuasan masyarakat terhadap kualitas layanan yang diberikan oleh penyelenggara pelayanan publik. Indeks Kepuasan Masyarakat sebagai berikut : Persyaratan, Sistem mekanisme, Waktu penyelesaian, Biaya/tarif, Produk spesifikasi jenis layanan, Kompetensi pelaksanaan, Perilaku pelaksanaan, Penanganan pengaduan saran dan masukan, serta sarana dan prasarana. Menurut (Permenpan Nomor.14 Tahun 2017 ). Dari uraian diatas maka peneliti tertarik melakukan penelitian dengan Judul“Pengaruh Bukti Fisik / Tangible(X1), Perhatian / Emphaty (X2), Kehandalan/Reliability(X3),DayaTanggap/Responsiveness(X4), Jaminan / Assurance (X5) Terhadap Kepuasan Masyarakat Pengguna Layanan Pada Kantor Urusan Agama Kecamatan Karau Kuala Tahun 2022”. Teori yang digunakan dalam penelitian ini yaitu Kualitas Pelayanan Menurut Lewis & Booms dalam Tjiptono & Chandran (2016). dan Kepuasan Masyarakat menurut Permenpan Nomor.14 Tahun 2017. Alat analisis yang digunakan yaitu Regresi Linier Berganda dengan menggunakan SPSS versi 25. Pada Tabel 4.50 Hasil yang diperoleh dalam perhitungan Regresi Linier Berganda adalah Y = 19,888 + 0,819 + 3,202 + 0,391 + (-2,123) + 1,257. Berdasarkan hasil analisis regresi pada tabel 4.60 diperoleh nilai (Fhitung > Ftabel) (18,635 > 2,38) dan nilai (Signifikan < 0,05) (0,000 < 0,05). Maka dapat disimpulkan Ho di tolak dan Ha diterima yang artinya Bukti Fisik/Tangible, Perhatian/Emphaty, Kehandalan/Reliability, Daya Tanggap/Responsivenes, Jaminan/Assurance secara simultan (bersama-sama) berpengaruh signifikan terhadap Kepuasan Masyarakat. Hipotesis dalam penelitian ini yaitu H₁=Bukti Fisik/Tangible secara parsial berpengaruh terhadap Kepuasan Masyarakat, H₂=Perhatian/Emphaty secara parsial tidak berpengaruh terhadap Kepuasan Masyarakat, H₃= Kehandalan/Reliability secara parsial tidak berpengaruh terhadap Kepuasan Masyarakat, H₄= Daya Tanggap/Responsivenes secara parsial tberpengaruh terhadap Kepuasan Masyarakat, H₅=Jaminan/Assurance secara parsial tidak berpengaruh terhadap Kepuasan Masyarakat, H₆= Kepuasan Masyarakat secara parsial berpengaruh terhadap Kepuasan Masyarakat. secara simultan. Abstract . Service quality is a measure of how well the level of service provided can be realized according to user expectations. Service quality itself is determined by the agency's ability to meet user needs and desires in accordance with user expectations. Community Satisfaction is a comprehensive measurement activity of the level of community satisfaction with the quality of services provided by public service providers. The Community Satisfaction Index is as follows: Requirements, Mechanism system, Completion time, Cost/tariff, Product specification type of service, Implementation competence, Implementation behavior, Handling complaints, suggestions and inputs, as well as facilities and infrastructure. According to (Permenpan No. 14 of 2017). From the description above, the researcher is interested in conducting research with the title "The Influence of Physical Evidence / Tangible (X1), Attention / Empathy (X2), Reliability / Reliability (X3), Responsiveness / Responsiveness (X4), Guarantee / Assurance (X5) On Community Satisfaction Service Users at the Karau Kuala District Religious Affairs Office in 2022". The theory used in this research is Service Quality According to Lewis & Booms in Tjiptono & Chandran (2016). and Community Satisfaction according to Permenpan Number 14 of 2017. The analytical tool used is Multiple Linear Regression using SPSS version 25. In Table 4.50 the results obtained in the calculation of Multiple Linear Regression are Y = 19.888 + 0.819 + 3.202 + 0.391 + (-2.123) + 1.257. Based on the results of the regression analysis in table 4.60, the value (Fcount > Ftable) (18,635 > 2,38) and the value (Significant < 0.05) (0.000 < 0.05). So it can be concluded that Ho is rejected and Ha is accepted, which means that Physical/Tangible Evidence, Attention/Emphaty, Reliability/Reliability, Responsiveness/Responsiveness, Guarantee/Assurance simultaneously (together) have a significant effect on Community Satisfaction. The hypothesis in this study is that H₁=Physical/ Tangible Evidence partially affects Community Satisfaction, H₂=Attention/Empathy partially does not affect Community Satisfaction, H₃= Reliability/Reliability partially does not affect Community Satisfaction, H₄= Responsiveness/Responsiveness Partially t has an effect on Community Satisfaction, H₅ = Guarantee/Assurance partially has no effect on Community Satisfaction, H₆ = Community Satisfaction partially has an effect on Community Satisfaction. simultaneously.the independent (X) Work Discipline and the dependent variable (Y) Employee Performance in the job training and workforce placement sections. Data processing techniques and data analysis used a Likert scale (questionnaire), simple linear regression analysis and simple regression coefficient test (t test) using the Windows application SPSS statistics version 25 program to test the results of calculations in the data analysis. The results obtained in the calculation of simple linear regression are Y = 18.628 + 0.553 x where the value (a) is 18.628; and the coefficient value (b) is 0.553. Then the results of tcount> from the above test show that tcount> ttable (3,374≥ t table 2,051) then Ho is rejected and Ha is accepted, meaning that there is an effect of Work Discipline on Employee Performance at the Manpower and Transmigration Service of South Barito Regency in 2021. Based on the conclusion, it can be seen that the effect of work discipline on employee performance in the Job Training Section and placement of workers at the Manpower and Transmigration Office of South Barito Regency in 2021 is important because it can improve employee performance in carrying out their respective duties according to job des.